Graham Greene : Fictions, Faith and Authorship. - Brennan, Michael G. (Bloomsbury Publishing, 2010)
In this significant rereading of Graham Greene's writing career, Michael Brennan explores the impact of major issues of Catholic faith and doubt on his work, particularly in relation to his portrayal of secular love and physical desire, and examines the religious and secular issues and plots involving trust, betrayal, love and despair. Although Greene's female characters have often been underestimated, Brennan argues that while sometimes abstract, symbolic and two-dimensional, these figures often prove central to an understanding of the moral, personal and spiritual dilemmas of his male charac.